2011
DOI: 10.1136/bmj.d1473
|View full text |Cite
|
Sign up to set email alerts
|

Dietary calcium intake and risk of fracture and osteoporosis: prospective longitudinal cohort study

Abstract: Objective To investigate associations between long term dietary intake of calcium and risk of fracture of any type, hip fractures, and osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
161
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(180 citation statements)
references
References 40 publications
13
161
1
5
Order By: Relevance
“…Blood samples were collected and prepared as plasma heparin, within the Swedish mammography cohort—clinical (SMC‐C; Dnr 2006/1490 and 2002/472c) 1, 10. The second set was from the Prospective Investigation of the vasculature in Uppsala Seniors cohort (PIVUS; Dnr 00–419 and 02–551) collected during 2001–2004 11.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Blood samples were collected and prepared as plasma heparin, within the Swedish mammography cohort—clinical (SMC‐C; Dnr 2006/1490 and 2002/472c) 1, 10. The second set was from the Prospective Investigation of the vasculature in Uppsala Seniors cohort (PIVUS; Dnr 00–419 and 02–551) collected during 2001–2004 11.…”
Section: Methodsmentioning
confidence: 99%
“…Osteoporosis, a chronic noncommunicable disease characterized by reduced bone density and increased bone fragility leading to higher risk of fracture, represents a major public health problem that is set to increase in importance as the proportion of elderly women and men in the population is on the rise 1, 2. In the European Union alone, approximately 3.5 million new fragility fractures occur each year, but the great majority of individuals at risk are not identified or treated 3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent longitudinal bone study has shown that calcium intakes of older adults [5] do not need to be much higher than 800 mg per day for optimal bone density measurements and low fracture rates, whereas intakes greater than 1200 mg per day result actually result in a greater rate of fractures. Another cross-sectional report of U.S. National Health and Nutrition Examination Survey data for 2005-2006 demonstrated that bone measurements of 50 to 80 year-olds were not related across a wide range of mean calcium intakes by quintiles from low to high total intakes of approximately 500 to 1200 mg per day [6].…”
Section: Calcium Intake and Bone Mass And Bone Fracturesmentioning
confidence: 99%
“…The recommended daily amount of calcium for people over 65 years is 1000 mg [6]. Table 8.1 shows the main sources of calcium with minimum amounts of 250 mg and 100 mg calcium, which should be a regular part of meals to meet the needs.…”
mentioning
confidence: 99%